Improving Students’ Learning Achievement Using the Collaborative Learning Model in the Batk Subject with Basic Competence Analyzing Flight Control in Class X D of SMKN 12 Bandung Academic Year 2019/2020 - Ferdinand Aruan (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to improve the ability of students who have not mastered a subject, especially BATK subjects, especially in the basic competency of analyzing Flight Control. The research approach used is observation and journal review. This data consists of quantitative data obtained from daily quiz tests given at the end of each cycle, both in Cycle I and Cycle II. The results of the BATK concept research, especially regarding the concept of Flight Control System and Flight Control System which are divided into 2 parts, namely Primary Control Surface and Secondary Control Surface, require activities that allow students to observe and discover for themselves the knowledge or material they have. will study. In presenting BATK material, it will be easier for students to understand if it is accompanied by pictures that are animated and presented systematically through multimedia. In BATK learning, the understanding of the concept of Flight Control System and Flight Control System is divided into 2 parts, namely Primary Control Surface and Secondary Control Surface which can be done through discussion activities sharing information with fellow friends in group activities. Collaborative learning models learning models can be done through face-to-face learning. Collaborative learning approach is a learning approach that can be used to increase the effectiveness of learning in schools.